Developing primary palliative care. Issue 7474 (4th November 2004) - Murray, Scott A; Boyd, Kirsty; Sheikh, Aziz; Thomas, Keri; Higginson, Irene J
Abstract : People with terminal conditions should be able to die at home with dignity